Innovation of Islamic Institutions in Managing the Transfer of Property Ownership Based on Sociopreneur - Kamilah, Athia Nur; Rinaima, Chetrine Alya; Fauziyah, Nur (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study examines the innovation of Islamic institutions in the management of property transfer with a sociopreneurship approach through a case study on As-Salihin Trustee Berhad in Malaysia. The aim of the research is to understand how social responsibility, ethical finance, and innovation are combined to strengthen sharia-based asset governance, as well as identify adaptable models in the inheritance system in Indonesia. The research uses a descriptive qualitative method with a case study design. Data was obtained through in-depth interviews, observations, and document analysis, then analyzed thematically. The results of the study show that As-Salihin implements strict sharia governance through the supervision of the Sharia Council, periodic audits, and technological innovations such as the Digital Faraid Calculator. Public literacy programs also increase public awareness of the importance of ethical estate planning. This study concludes that As-Salihin plays a role as a sociopreneur institution that combines profitability, sharia compliance, and social empowerment. These findings offer a transparent and replicable model of inheritance governance in Islamic asset management institutions in Indonesia.